2019
DOI: 10.22159/ijap.2019v11i4.33071
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study of Hair Tonic and Gel Formulation of Angiopteris Evecta as a Hair Growth Stimulant

Abstract: Objective: Previous research has proven that the water fraction of the Angiopteris evecta root has hair growth activities. The objective of this research was to determine the formula of gel and hair tonic preparations of pakis munding (Angiopteris evecta L.) which met the requirements as a pharmaceutical preparation, good and effective in stimulating hair growth. Methods: Formulation of hair tonic and gel preparations were made using 7.5, 10.0, and 12.5 % of A. Evecta root water extracts as active compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
3
0
3
Order By: Relevance
“…The concentrations of water fractions of cocoa pods used were 7.5%, 10.0%, and 12.5%. The choice of concentration was based on the dose test according to previous studies [ 29 , 30 ]. The results of testing hair growth stimulating activity in rabbits ( Table 3 and Figure 1 ) showed that positive control and test preparations had better hair growth than normal control and negative control.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of water fractions of cocoa pods used were 7.5%, 10.0%, and 12.5%. The choice of concentration was based on the dose test according to previous studies [ 29 , 30 ]. The results of testing hair growth stimulating activity in rabbits ( Table 3 and Figure 1 ) showed that positive control and test preparations had better hair growth than normal control and negative control.…”
Section: Discussionmentioning
confidence: 99%
“…Konsumen cenderung menyukai produk kosmetik yang mudah diaplikasikan seperti tonik rambut dibanding jenis produk lainnya. Selain itu, sediaan tonik rambut mudah diabsorpsi oleh kulit kepala dan tidak menghasilkan residu yang dapat menyebabkan iritasi (Mustarichie et al 2019). Tonik rambut dapat diformulasikan dari material sintetis maupun alami.…”
Section: Pendahuluanunclassified
“…Namun, hair tonic yang beredar dipasaran masih banyak yang mengandung zat sintesis seperti minoxidil. Minoxidil umum dipakai sebagai obat topikal pada kulit kepala untuk mengurangi kerontokan rambut dilaporkan dapat menyebabkan reaksi alergi, gatal-gatal dan dermatitis (Rossi et al, 2012;Venkatesh et al, 2020;Mustarichie et al 2019).…”
Section: A Pendahuluanunclassified